Sistem Pendukung Keputusan Siswa Berprestasi menggunakan Metode Simple Multi Attribute Rating Technique berbasis Web - Aisa, Sitti; Akhriana, Asmah; Ramadhani, Dwi Qadri; Siola, Mario; Mashud, Mashud (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
As one of the private schools in Makassar, Elim Christian High School, the assessment process carried out by teachers on students is still done manually or by recording. Reviewing the assessment of students with academic achievements includes assessments in several subjects as well as non-academic achievements in terms of arts, sports and extracurricular activities. This research aims to design a decision support system application that can assist teachers in managing final grades to determine students with academic and non-academic achievements using a web-based application, using the Simple Multi Attribute Rating Technique Method. The research model included is the SDLC model which starts from analysis, design, implementation, testing and evaluation. Analyze student data and teacher grades. The implementation section creates a web-based application that can carry out the process of selecting the best students. Testing uses black box testing which tests all menus, ensuring the output and functionality are appropriate. The data analysis technique entered is quantitative analysis. Where, quantitative analysis in the form of data is obtained by collecting student data and their grades. The findings are in the form of an application that helps teachers provide recommendations for students who excel both academically and non-academicly in the specified assessment categories. By implementing the Simple Multi Attribute Rating Technique method in implementing the decision support system application, it makes it easier for teachers to determine outstanding students.